The challenge of recruiting in primary care for a trial of telemonitoring in asthma: an observational study - Malhotra, Shweta (Pragmat Obs Res, 2012)
AIM: Achieving target recruitment in randomized controlled trials (RCTs) is challenging. This paper compares our experience of recruiting for an RCT with the predictions made in our proposal. METHODS: Participating UK primary care practices searched their computer databases to identify patients (12 years and over) with asthma who may be poorly controlled. Postal invitations were sent to all patients identified. Respondees were prescreened by phone, to assess their asthma control and establish their mobile phone suitability. Potentially eligible patients were booked for a trial recruitment visit. RESULTS: We recruited 288 patients (2.4% of those invited) across 32 practices, with a total list size of 311,926 patients. This compares to our predicted recruitment of 312 patients from a population of 72,000 patients in six to eight practices. In addition to the recognized problem of poor response rates, the major challenges were insufficiently discriminating computer searches and incompatibilities between mobile phone handsets, networks and the asthma application. CONCLUSION: Our data have implications for clinicians, managers, and researchers in primary care. Researchers in this area may wish to consider our data when designing their recruitment strategies. Improved coding of asthma morbidity data in clinical practice would ease identification of poorly controlled patients, both for clinical interventions and recruitment to trials. If telehealth is to become mainstream, there needs to be standardization of applications, operating platforms, and network capabilities.